Narratives, Nations, and Other World Products in the Making of Global History - Adelman, Jeremy; Eckert, Andreas (Bloomsbury Publishing Plc, 2024)
Explaining how nations and narratives have been the products of transnational, cross-border forces of migration and cultural exchange, this open access volume presents a global history of the basic ideas that govern our understanding of the modern world and highlight the power of narratives in world history.From the Enlightenment forward, the nation and other global concepts have been conjured and repurposed to manage and make sense of what we now call globalisation. The authors in this volume show how social categories such as empire, race and labour were the centerpiece subjects of collective narratives. For the past two centuries, the practices of shared storytelling aimed to make sense of how groups like nations fit in the wider world. This volume explores how they created bonding narratives for co-members of these groups and bridging stories to explain how groups should relate to each other through trade, war, peace, and other worldmaking processes. The ebook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com. Open access was funded by Princeton University, USA